Development of a Web-Based Village Administration Information System With an AI Chatbot Feature - Putri Arum Sari; Irma Salamah; Lindawati Lindawati (Universitas Malikussaleh, 2026)
The rapid development of information technology has encouraged government institutions to improve administrative efficiency and public service quality through digital transformation. However, many village administrations still rely on manual data management practices, resulting in inefficient information retrieval, data redundancy, and limited public access to administrative services. This study aims to develop a web-based village administration information system integrated with an Artificial Intelligence (AI) chatbot feature to support administrative management and public information services. The research employed a system development approach consisting of problem identification, literature study, data collection, system analysis, system design, implementation, and testing. The system was developed using HTML, CSS, JavaScript, PHP, and MySQL, while the chatbot functionality was implemented through Application Programming Interface (API) integration. The developed system integrates several administrative modules, including employee management, population data management, family card management, correspondence services, statistical information reporting, and AI-based information services. System evaluation was conducted using the Black Box Testing method to verify functional correctness. The testing results showed that all implemented modules operated according to the specified requirements and successfully performed their intended functions. The AI chatbot was able to provide administrative information in real time and support citizen interaction without requiring direct assistance from village officers. The developed system contributes to improving administrative efficiency, facilitating information retrieval, increasing transparency, and supporting the digital transformation of village public services through the integration of administrative management and intelligent information services within a unified web-based platform.